Integrated nitrogen management through biofertilizers in cabbage (Brassica oleracea var capitata)* - SOOD, RUCNU; V, VIDYASAGAR (The Indian Journal of Agricultural Sciences, 2011)
A study was carried out during the years 2002-03 and 2003-04 to study the response of integrating biofertilizers with chemical nitrogen fertilizer in cabbage. The treatment combinations comprised 3 nitrogen levels (80, 60 and 40% of the recommended dose), 2 biofertilizers (Azotobacter and Azospirillum) and 2 methods of biofertilizer application (soil and seed application) along with the control (recommended dose of chemical fertilizer). The treatment combination 80% N + Azospirillecrn as soiVseed application was the best giving marketable yield atleast at par with the control. The biofertilizer Azotobacter or Azospirilhtm could effect economy up to 20% of the recommended dose of nitrogen under the agroclimatic conditions prevailing at Palampur.